Implementation of Online Learning Management For Elementary School Students in Rural Times During The Covid-19 Pandemic - Pribadi, Luthfi Audia; Nurdin, Diding; Rahyasih, Yayah (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
The focus of research is on teachers as managers in managing online learning during the Covid-19 pandemic. This study uses a descriptive-qualitative approach, namely describing and revealing existing facts and then describing them descriptively with words or descriptions. The results of the study indicate that the application of management functions can minimize the impact of online learning in the village. The existence of innovative learning methods that are considered effective in teaching and learning activities. Troubleshooting the flow of communication between schools and parents. The research was conducted in a rural area, namely SDN Negla (Kertasari) Bandung Regency, West Java Province. What is new in this research is that it is carried out in rural areas where the majority of human resources have minimal technological knowledge.